Quantitative Analysis of Microstructures and Reaction Interfaces on Composite Cathodes in All-Solid-State Batteries Using a Three-Dimensional Reconstruction Technique - Choi, Sungjun; Jeon, Minjae; Ahn, Junsung; Jung, Wo Dum; Choi, Sung Min; Kim, Ji-Su; Lim, Jaemin; Jang, Yong-Jun; Jung, Hun-Gi; Lee, Jong-Ho; Sang, Byoung-In; Kim, Hyoungchul (American Chemical Society, 2018)
The composite cathode of an all-solid-state battery composed of various solid-state components requires a dense microstructure and a highly percolated solid-state interface different from that of a conventional liquid-electrolyte-based Li-ion battery. Indeed, the preparation of such a system is particularly challenging. In this study, quantitative analyses of composite cathodes by three-dimensional reconstruction analysis were performed beyond the existing qualitative analysis, and their microstructures and reaction interfaces were successfully analyzed. Interestingly, various quantitative values of structure properties (such as the volume ratio, connectivity, tortuosity, and pore formation) associated with material optimization and process development were predicted, and they were found to result in limited electrochemical charge/discharge performances. We also verified that the effective two-phase boundaries were significantly suppressed to similar to 23% of the total volume because of component dispersion and packing issues.
Keywords: LITHIUM BATTERIES; ELECTROCHEMICAL PROPERTIES; LICOO2 ELECTRODE; ION CONDUCTORS; PERFORMANCE; TOMOGRAPHY; STABILITY; PROGRESS